2023
DOI: 10.5093/apj2023a5
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Adolescents who Abuse their Parents: A Gender-based Analysis

Abstract: Adolescent-to-parent violence (APV) is still the most understudied type of domestic violence, although reports filed by victimized parents and youths serving judicial measures for this reason are increasing. The aim of this study is to assess the differential profile of boys and girls who have and have not reported APV in a community sample, following studies showing differences between both genders in initiating and maintaining offending behavior. To this end, each gender was assessed separately in relation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…According to George and Mallery [56], thresholds are established for Cronbach's alpha: values below 0.50 are considered unacceptable, values between 0.50 and 0.60 are considered poor, and values between 0.60 and 0.70 are questionable, and therefore, values above 0.70 are considered acceptable, values above 0.80 are considered good, and values above 0.90 are considered excellent. In our analysis, no studies reported unacceptable values for internal consistency, although four studies presented estimates that were considered questionable [29,38,51,53].…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…According to George and Mallery [56], thresholds are established for Cronbach's alpha: values below 0.50 are considered unacceptable, values between 0.50 and 0.60 are considered poor, and values between 0.60 and 0.70 are questionable, and therefore, values above 0.70 are considered acceptable, values above 0.80 are considered good, and values above 0.90 are considered excellent. In our analysis, no studies reported unacceptable values for internal consistency, although four studies presented estimates that were considered questionable [29,38,51,53].…”
Section: Discussionmentioning
confidence: 75%
“…The highest internal reliability estimate was reported by Calvete et al [15], with an alpha of 0.93. However, the two measures yielded alphas below the minimum acceptable threshold of 0.70 (Calvete et al [29], α = 0.610 and α = 0.680; Martín, and Cortina [38] α = 0.690) An additional three measures were excluded to provide inadequate cases-per-item ratios, violating the minimum sample size requirements relative to the scale length with regard to the studies by Ghanizadeh and Jafari [32] A total of 13 eligible studies reported Cronbach's alpha values for father-specific scales, but 16 Cronbach's alpha measures were found, and 4 measures were excluded because they did not meet the criteria of an alpha of > 0.70 or a sample size of a 10:1 cases-per-item ratio. Finally, analyses were performed using 12 Cronbach's alpha measures.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Perpetrators' gender has been addressed in APV research to analyze differences in the amount and type of violence exerted by boys and girls [14]. Some studies have also explored the differential characteristics of boys and girls who are violent with their parents, both in judicial [15] and in community samples [16][17][18]. However, it has not yet been studied whether the gender of the perpetrator affects APV's social perception.…”
Section: Introductionmentioning
confidence: 99%